2020
DOI: 10.1111/dth.14163
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional botulinum toxin A injection for treating nodular scabies

Abstract: Scabies, a neglected tropical disease, is a highly contagious parasitic skin disease caused by the mite Sarcoptes scabiei. 1,2 Nodular scabies is a well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1,7,8 The strategic treatments for NS and its itch are limited and remain challenging sometimes, which include potent topical, intralesional, and systemic corticosteroids, topical calcineurin inhibitors and crotamiton, cryotherapy, surgical excision of the lesions, and even injection of intralesional botulinum toxin A used alone or in a different combination, showing various response with possibility of recurrence. 1,7,11,15,16 The effect of antihistamines for scabies is limited, however, which can be used to improve the patient's somnus and help alleviate pruritus. 1,3,4,7,15,16 In rare instances, the sarcoptic nodules are difficult to eradicate as in the present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7,8 The strategic treatments for NS and its itch are limited and remain challenging sometimes, which include potent topical, intralesional, and systemic corticosteroids, topical calcineurin inhibitors and crotamiton, cryotherapy, surgical excision of the lesions, and even injection of intralesional botulinum toxin A used alone or in a different combination, showing various response with possibility of recurrence. 1,7,11,15,16 The effect of antihistamines for scabies is limited, however, which can be used to improve the patient's somnus and help alleviate pruritus. 1,3,4,7,15,16 In rare instances, the sarcoptic nodules are difficult to eradicate as in the present.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 7 Histamine pathway is not thought the main mediator that contributed to the pathomechanism of sarcoptic itch, 4 , 7 although antihistamines have been used for the treatment of such conditions. 1 , 3 , 4 , 7 , 15 , 16 However, non-histaminergic pathways such as host–mite interaction including both type I and type IV hypersensitivity reaction, and secondary microbial infection and never sensitization are considered to be the main reasons for scabies pruritis. 7 , 11 , 15 The recent studies from the animal model showed that transient receptor potential vanilloid-1, transient receptor potential ankyrin 1, protease-activated receptor 2, and tryptase + cells had played important roles in the non-histaminergic itch of scabies.…”
Section: Discussionmentioning
confidence: 99%
“…Janus Kinase (JAK)) inhibitors 144 TRP channels TRP channel modulators (e.g. topical capsaicin, topical calcineurin inhibitors, topical camphor, topical menthol, topical strontium hydrogel formulation (TriCalm TM ), and botulinum toxin) [152][153][154] successful in reducing localized scabies itch (i.e. nodular scabies).…”
Section: Control Of Scabies Itch (Table 2)mentioning
confidence: 99%
“…nodular scabies). [152][153][154] The topicals (capsaicin, in particular) may cause a transient burning sensation and should be applied with care (i.e. avoid excoriated areas).…”
Section: Control Of Scabies Itch (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation